Retrospective analysis of four-year injury data from the Infantry Training Centre, Catterick. Issue 1 (22nd August 2017) - Heagerty, Robert; Sharma, J; Cayton, J; Goodwin, N
Abstract : Introduction: Musculoskeletal injury (MSKI) represents a considerable threat to the effectiveness and productivity of military organisations globally. The impact on the medical chain, occupational disposal with associated loss of working days and associated financial burden have far-reaching consequence. The moral and legal responsibility to reduce avoidable injuries through risk assessment and prevention strategies is fundamental to governance and a key component of best practice. Methods: A retrospective observational analysis was performed of 4101 MSKIs presenting from a total inflow of 10 498 British Army Infantry recruits recorded over four consecutive training years between 2012 and 2016. Injury incidence, site, type and week of training were recorded and analysed. Results: The total incidence of all MSKI was observed as 39.1%. Overuse injuries were the most common subclassification of injury type (24.5%), followed by trauma (8.8%) and then stress fractures (5.7%). Causes of medical discharge over a four-year cumulative incidence were from overuse injuries (59.3%), stress fractures (21.5%) and trauma (19.2%). 45.5% of all MSKIs presented within the first eight weeks of training. Conclusions: MSKI data highlighted the requirement for a comprehensive service evaluation of the Combat Infantryman's Course and subsequent justification for the introduction of an injury prevention intervention — Project OMEGA.